2010
DOI: 10.3340/jkns.2010.47.3.191
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Assessment of Adult Patients with Shunted Hydrocephalus

Abstract: Objective : This study is planned to determine the neurocognitive difficulties of hydrocephalic adults. Methods : The research group contained healthy adults (control group, n : 15), and hydrocephalic adults (n : 15). Hydrocephalic group consisted of patients with idiopathic aquaduct stenosis and post-meningitis hydrocephalus. All patients were followed with shunted hydrocephalus and not gone to shunt revision during last two years. Results : Neuropsychological assessment of hydrocephalic patients demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The serial digit learning tests (SDL Test) is useful in evaluating cognitive processing, such as learning and short term memory, and it has been used in various disease groups, like depression and hydrocephaly (Bakar and Bakar 2010;Demir et al 2013). This test has also been used in OSAS to assess cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…The serial digit learning tests (SDL Test) is useful in evaluating cognitive processing, such as learning and short term memory, and it has been used in various disease groups, like depression and hydrocephaly (Bakar and Bakar 2010;Demir et al 2013). This test has also been used in OSAS to assess cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…The Bender-Gestalt test was administered mainly to evaluate visuomotor integration skills. The total score was determined using the scoring system of Bakar and Bakar [42 ]and Lacks and Newport [43]. …”
Section: Methodsmentioning
confidence: 99%
“…In our study, we also found hypoactivity, reduced rotarod performance and a loss of body weight in mice immediately prior to death. In humans, gait abnormalities, motor disorders and memory and cognitive deficits are the most common behavioral changes; however, these behavioral deficits are associated with overt hydrocephalus and are likely due to the compression of brain tissue (e.g., the cortex, hippocampus and cerebellum) that is common with severe hydrocephalus [52] [56] .…”
Section: Discussionmentioning
confidence: 99%